The Companions We Keep: A Situational Analysis and Proposed Typology of Companion Animal Cruelty Offenses. Issue 6 (3rd June 2018) - Grugan, Shannon T.
ABSTRACT: Abuse and neglect of nonhuman companion animals (i.e., pets) are not well understood as crime phenomena even though the keeping of animals as companions is relatively commonplace, reports of abuse and neglect are not at all rare, and the media generally serves to reinforce this notion that cruelty is a frequently occurring and widespread problem. This study is a typological content analysis of situational factors in 179 cases of companion animal cruelty featured in news media reported in the United States during the first six months of 2013.